Morphobiological analysis of Trichuris vulpis (Nematoda, Trichuridae), obtained from domestic dogs - V. А. Yevstafieva; S. O. Kravchenko; B. V. Gutyj; V. V. Melnychuk; P. N. Kovalenko; L. B. Volovyk (Regulatory Mechanisms in Biosystems, 2019)
The parasitic nematode Trichuris vulpis Frölich, 1789 is the pathogen of trichuriasis in domestic and wild carnivores, and humans. This helminth species is distributed world-wide in populations of domestic dog (Canis lupus familiaris). The prevalence of T. vulpis in dogs depends to a large degree on the morphofunctional and biological adaptations of the parasite which support its high survivability in various environmental conditions. The present study considers the species-specific peculiarities of morphology, and metric parameters of the mature and embryonic stages of Trichuris nematodes parasitizing in C. lupus familiaris. We studied the periods of stages of development and infectious egg formation, and their survivability under optimal conditions for T. vulpis in laboratory culture. The differential characteristics of both female and male adult T. vulpis nematodes include the metric characteristics of cuticular protrusions at the surface of the anterior body part. The male T. vulpis nematodes can be distinguished from males of other species by the specifics of spicule sheath ornamentation, the shape and size of spicule, and the width of spicule sheath at different sections. In identification of the female nematodes of this species, it is necessary to consider the presence and size of papillary processes in the vulval area and metric parameters of vulva location. Nine metric characters of sexual dimorphism are described for T. vulpis nematodes. In laboratory conditions, five embryonic stages were observed for T. vulpis: protoplast, blastomere cleavage, and formation of bean-like embryo, larva and mobile larva. These stages are characterized by specific morphological features. The egg develops to the infectious stage at 27 °С in 18 days of culture, and their survivability is up to 76.6%. The egg development is associated with changes in their metric characters, such as decreasing egg length and width of egg shell, and increasing egg width and egg plug width.